Influence of renewable energy and natural resources on climate change: The role of green innovation in China - Jiang, Dayang; Shu, Hansong; Fan, Yifan; Dong, Yuting; Li, Haiwei (Frontiers in Environmental Science, 2022)
The economic progress of China cannot be denied; however, deteriorating environmental quality is the primary concern to be addressed. Since the last few years, China’s legislators have intended to facilitate green transformation by sustaining natural resources and ensuring renewable energy consumption. Therefore, this study explores the impact of renewable energy, natural resource green innovation, and economic growth on ecological footprints in China. The bootstrap autoregressive distributed lag (ARDL) model has been deployed by taking the quarterly data ranging between 1990Q1 and 2020Q4. The results reveal that by enhancing green innovation, China can transform its economy into a clean environment. Similarly, the effective utilization of renewable energy consumption is indispensable to reducing the ecological footprint in the long run. Moreover, the Error Correction Term (ECT) is significantly negative, confirming a stable long-run equilibrium relationship between model variables. Similar results are found in the short run; however, the marginal impact of all variables is stronger in the long run. It implies that long-term planning is imperative in China for optimal benefits from renewable energy and green technologies.